Physico-chemical and spectroscopic quality assessment of compost from date palm (Phoenix dactylifera L.) waste valorization. (15th June 2020) - Abid, Wadii; Mahmoud, Imen Ben; Masmoudi, Saoussan; Triki, Mohamed Ali; Mounier, Stéphane; Ammar, Emna
Abstract: Organic matter (OM) is a vital component for a healthy soil, its lack arise a major problem for farmers who need to use commercialized fertilizers with high costs. Considering circular economy approach and for increasing OM availability, water soaked date palm waste was co-composted with goat manure in aerated windrow to produce a soil organic amendment. The OM biodegradation was mainly controlled based on biological parameters and spectroscopic techniques. The results showed a rapid temperature increase during the first week, and a relatively long compost maturity phase. The OM content reduction was of 36% and C/N ratio shifted from 60 to 20 at the process end. During the composting process, the specific ultraviolet absorbance SUVA254, SUVA269 and the SUVA280 values increase confirmed the OM and hydrophilic compounds degradation, as well as substrate content oxidation into aromatic compounds. The Fourier Transform Infrared Spectroscopy (FTIR) analyses of the different samples collected during the process exhibited both OM biodegradation and mineralization. The 3 absorption ratios 1650/2845, 1525/2925 and 2920/1640 confirmed an aromaticity increase by aromatic structures biosynthesis, such as humic-like and fulvic-like substances, with the decomposition/transformation of aliphatic components, polysaccharides, and alcohols. Fluorescence excitation-emission matrix (FEEM) spectroscopy coupled with parallel factor analysis (PARAFAC) evidenced the dissolved organic matter (DOM) humification. A four-component model was obtained, i.e. humic-like component (S1, S2 and S3) and fulvic-like component (S4). The produced compost didn't exhibit any phytotoxicity evidenced by cress seed germination index exceeding 80%. All the analyses confirmed the good quality of the compost issued from mixed date palm waste and goat manure. Graphical abstract: Image 1 Highlights: This work aims at informing about the palm waste composting feasibility. Crushed soaked date palm waste can be managed by co-composting with goat manure. DOM transformation was assessed by UV, FTIR and fluorescence spectroscopy. Organic residues composting mixture resulted in a high product quality. Chemical and biological analyses confirmed the raw organic matter sustainability.